Pakatan forced to amend manifesto: Boo-Boos: Opposition criticised for 'leaving out' many promises - Ariff, Syed Umar (New Straits Times, 2013)
A BARRAGE of criticisms on its recently launched election manifesto have led amendments to silence detractors.